FAKTOR-FAKTOR YANG MEMENGARUHI PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Kusumawardani, Ira; Sudana, I Putu (E-Jurnal Akuntansi; Vol 19 No 1 (2017), 2017)
Corporate Social Responsibility is a concern for the company to maintain its legitimacy and reputation. The purpose of this study is to empirically demonstrate the effect of foreign ownership, independent board of directors, company size, and profitability to CSR disclosure. Data for this study was taken from the website of Indonesian Stock Exchanges. Taken with non-probability sampling method, 40 observations were obtained. Data is analysed using multiple linear regression. This sudy concluded that foreign ownership, independent board, and profitability have no effect on CSR disclosure, while the size of the company has a positive influence on CSR disclosure. Thhis study provides a basis for management to consider policies in expressing the intensity of CSR disclosure especially for large companies to gain legitimacy from its stakeholders. For bigger companies, the demands of stakeholders on extensive disclosure tend to be larger.
Keywords: Foreign Ownership, The Board of Independent Commissioners, Company Size, Profitability, Corporate Social Responsibility